Dual‐Polymer‐Functionalized Nanoscale Graphene Oxide as a Highly Effective Gene Transfection Agent for Insect Cells with Cell‐Type‐Dependent Cellular Uptake Mechanisms. (21st May 2013) - Zhang, Jing; Feng, Liangzhu; Tan, Xiaofang; Shi, Xiaozhe; Xu, Ligeng; Liu, Zhuang; Peng, Rui
<x xml:space="preserve">Abstract</x> Efficient and safe gene transfection carriers, especially for hard‐to‐transfect cells, are urgently demanded in basic biological research and gene therapy applications. Many insect cell lines widely used in molecular cell biology exhibit relatively low transfection efficiencies when treated by conventional non‐viral agents. Herein, we develop a novel gene delivery vector by coating graphene oxide (GO) with both polyethylene glycol (PEG) and polyethylenimine (PEI), obtaining a dual‐polymer‐functionalized nanoscale GO (nGO‐PEG‐PEI) to transfect insect cells. While exhibiting remarkably reduced cytotoxicity compared with PEI, nGO‐PEG‐PEI, when used as the plasmid DNA transfection agent to treat Drosophila S2 cells, offers ≈7‐fold and ≈2.5‐fold higher efficiency compared with those achieved by using bare PEI and Lipofectamine 2000, a widely used commercial transfection agent, respectively. Interestingly, the advantages of nGO‐PEG‐PEI are even more dramatic when transfecting cells with lower‐quality linearized DNA. It is revealed that nGO‐PEG‐PEI/pDNA complexes enter insect cells via a unique pathway working even at a low temperature, rather different from their entry into mammalian adherent cells. Our results encourage the development of nano‐GO‐based gene carriers to treat special types of hard‐to‐transfect cells (e.g., insect cells), and indicate that nanomaterials would enter cells by cell‐type‐dependent mechanisms, which merit significantly more future attentions.